Tumor Size Still Impacts Prognosis in Breast Cancer With Extensive Nodal Involvement - Liu, Yin; He, Min; Zuo, Wen-Jia; Hao, Shuang; Wang, Zhong-Hua; Shao, Zhi-Ming (Frontiers in Oncology, 2021)
Background and purpose Although tumor size and nodal status are the most important prognostic factors, it is believed that nodal status outperforms tumor size as a prognostic factor. In particular, when patients have a nodal stage greater than N2 (more than 9 positive lymph nodes), it is well accepted that tumor size does not retain its prognostic value. Moreover, some physicians have speculated that for tumors staged N2 or greater, the smaller the tumor is, the more aggressive the tumor. Thus, this study aims to investigate the prognostic value of tumor stage (T stage) in patients with extensive nodal involvement and to compare the survival of T4NxM0 and TxN3M0. Patients and methods Female breast cancer patients with 9 or more positive lymph nodes or with T4 tumors were identified in the SEER registry between 2010 and 2015. The effect of T stage on breast cancer-specific survival (BCSS) was assessed using the Kaplan-Meier survival curve method and risk-adjusted Cox proportional hazard regression modeling. Survival comparison of T4NxM0 and TxN3M0 patients was also achieved using the Kaplan-Meier survival curve method and risk-adjusted Cox proportional hazard regression model. Results Overall, 21696 women with N2-3 tumors were included from 284073 patients. T stage, nodal stage (N stage), ER, PR, HER2 and grade were all independent prognostic factors. Notably, HER2 positivity was correlated with better BCSS possibly due to the wide adoption of anti-HER2 therapy. In the two subgroups, namely, women staged as T1-3N2 and women staged as T1-4N3, T stage was a significant negative prognostic factor independent of ER, PR, HER2 and grade. Moreover, 8328 women staged as T4 with different nodal statuses were also identified from the whole database. When we compared T4Nx with TxN3, it was found that T4 tumors exhibited worse outcomes than N3 tumors independent of other prognostic factors. Conclusions: In patients with extensive nodal status, tumor stage remains a prognostic factor independent of other factors. In patients with T4Nx or TxN3 tumors, T4 tumors exhibit worse outcomes than N3 tumors independent of other prognostic factors. The AJCC staging system should be modified based on these findings.